Research trends in vulnerability studies from 2000 to 2019: Findings from a bibliometric analysis. (1st April 2021) - Kim, Byeong Je; Jeong, Seunghoo; Chung, Ji-Bum
Abstract: Vulnerability is a principal concept widely applied in disaster risk management and related studies to understand disaster risks. Vulnerability is understood as having various meanings ranging from direct disaster damage to indirect factors that affect damage, such as exposure, susceptibility, and adaptation. As no universal definition of vulnerability exists, the concept has become diversified, which has led to considerable confusion and contention among scholars. Accordingly, this study conducts a bibliometric analysis to investigate the historical changes in disaster risk management's vulnerability concept and its related fields between 2000 and 2019. This work collected bibliographic data by searching for disaster-related publications with the keyword vulnerability through an online database. The topic networks were constructed by using collected bibliographic data to identify research trends of vulnerability-related studies. This study found that the number of vulnerability-related publications increased rapidly from 2010. Among the various topics, climate change, adaptation, and resilience have become important research subjects in vulnerability-related studies, while topics related to structural mitigation had received less attention regarding the number of publications by the mid-2010s. These spotlighted topics shifted toward adaptation and resilience following international agreements. The proposed method can help an efficient understanding of the research trends in vulnerability-related studies. The analyzed trend is expected to provide scholars in this domain with a better insight into vulnerability studies. Highlights: Bibliometric analysis revealed changes in the vulnerability concept from 2000 to 2019. Structural mitigation topics changed to non-structural mitigation/adaptation topics. Shift toward climate change, adaptation, and resilience in line with global trends. Framework aids insight into quantitative/relational changes in vulnerability trends.